A Study of Occupational Structure and Livelihood among Tibetan People in-Exile in India - Vinod Kumar Sharma; Nikesh Sharma (PT FORMOSA CENDEKIA GLOBAL, 2022)
Tibetans in exile i.e Nepal, Bhutan, India and other parts of the world are those, who along with the Dalai Lama, escaped their own native place after Chinese aggression or occupation of Tibet in the year of 1959. Therefore, they have been forced to move in Exile and with the time span, the people of Tibet community have been settled in 41 Tibetan settlements located in different parts of India like Karnataka, Himachal Pradesh, Uttarakhand, Arunachal Pradesh, Jammu and Kashmir, West Bengal etc. But as far as Nepal and Bhutan is concerned, 17 Tibetans settlements are located in Nepal and 7 in Bhutan, where Tibetan refugees have been resided (survey report of 2019). Whereas Dharamshala is the capital city of Tibetan Govt. in exile and also considered as the largest settlement of North India in Himachal Pradesh having the 8,517 population number comprising 4,424 male and 4,093 female(2019). But as per the survey report of 2019, the present population of Tibetans outside Tibet is 145100, out of which one lakh estimated population of Tibetans residing in India. Apart from India near about 16,000 in Nepal, 1800 in Bhutan and 25,000 Budhist population living in other parts of the world.